2020
DOI: 10.1038/s41467-020-16298-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial uncoupler BAM15 reverses diet-induced obesity and insulin resistance in mice

Abstract: Obesity is a health problem affecting more than 40% of US adults and 13% of the global population. Anti-obesity treatments including diet, exercise, surgery and pharmacotherapies have so far failed to reverse obesity incidence. Herein, we target obesity with a pharmacotherapeutic approach that decreases caloric efficiency by mitochondrial uncoupling. We show that a recently identified mitochondrial uncoupler BAM15 is orally bioavailable, increases nutrient oxidation, and decreases body fat mass without alterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 55 publications
9
92
0
Order By: Relevance
“…In support of this, oral dosing of BAM15 (∼85 mg/kg/day) was independently shown to prevent diet-induced obesity and improve glycemic control through alterations in whole-body energy expenditure, reduced adiposity, and AMPK-mediated suppression of WAT lipogenesis [ 112 ], supporting a crucial role of adipose tissue in mediating BAM15's beneficial effects. Interestingly, previous studies did not demonstrate an adipose-targeted depot for BAM15-mediated uncoupling [ 111 ]; however, differences in dose routes and pharmacokinetic study designs could explain these discrepancies.…”
Section: Therapeutic Relevance Of Mitochondrial Uncouplersmentioning
confidence: 97%
See 2 more Smart Citations
“…In support of this, oral dosing of BAM15 (∼85 mg/kg/day) was independently shown to prevent diet-induced obesity and improve glycemic control through alterations in whole-body energy expenditure, reduced adiposity, and AMPK-mediated suppression of WAT lipogenesis [ 112 ], supporting a crucial role of adipose tissue in mediating BAM15's beneficial effects. Interestingly, previous studies did not demonstrate an adipose-targeted depot for BAM15-mediated uncoupling [ 111 ]; however, differences in dose routes and pharmacokinetic study designs could explain these discrepancies.…”
Section: Therapeutic Relevance Of Mitochondrial Uncouplersmentioning
confidence: 97%
“…demonstrated that BAM15 is orally bioavailable and reduces body weight due to increases in whole-body energy expenditure and reductions in fat mass. BAM15 administration to Western diet-fed mice led to reductions in hypertriglyceridemia, hepatic steatosis, and hepatic inflammation as well as improvements in whole-body insulin sensitivity without altering body temperature or renal/hepatic toxicity [ 111 ]. While the exact mechanisms of BAM15's anti-obesity effects remain to be determined, the authors attributed these beneficial effects to BAM15-mediated uncoupling in hepatocytes and increases in hepatic substrate utilization.…”
Section: Therapeutic Relevance Of Mitochondrial Uncouplersmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in this field is very active and several novel approaches to stimulating energy expenditure in order to improve metabolic health have been reported while this article was being finalized. Treating mice with an orally bioavailable mitochondrial uncoupler, BAM15, was shown to increase nutrient oxidation, and decrease adiposity without altering food intake, and improve insulin sensitivity [ 95 ]. These actions reversed diet-induced obesity and would be expected to promote healthy aging.…”
Section: Studies Of the Regulation Of Development And Function Of Bromentioning
confidence: 99%
“…Over the last 40 years, the prevalence of obesity has almost tripled worldwide 3 . The development of obesity is closely associated with multiple diseases, such as type 2 diabetes, hepatic steatosis, cardiovascular diseases, and even cancer [4][5][6][7][8][9] . Hence, obesity is a great threat to public health and causes an economic burden for society.…”
Section: Introductionmentioning
confidence: 99%